(untitled) (Research, Society and Development, 2022)
To verify the inference of osteopathic manipulative treatment on heart rate in newborns hospitalized in a maternal and child care ward. This is a qualitative-quantitative, longitudinal, randomized clinical trial, carried out at the University Hospital of Cascavel, Paraná, Brazil. This study was submitted and approved in 2021 by the Research Ethics Committee, in compliance with resolution 466/12. Data from the instruments were tabulated in Microsoft Office Excel® and exported to SPSS, version 20.0. 70 full-term neonates were analyzed and randomly allocated into three groups, with G1 the intervention was Static Touch, G2 was the Craniosacral osteopathic protocol, and G3 was the Osteopathic Manipulative Treatment. The results of this research showed that the static touch did not produce a significant change in the heart rate of newborns. The craniosacral osteopathic protocol and OMT showed a tendency to reduce heart, with the valuation tending to return to initial patterns after 10 minutes of the intervention and after 24 hours, respectively, suggesting that a single osteopathic intervention can induce beneficial effects on the heart rate of term newborns.